DOCUMENT SUMMARIZER - TENG, CHENG HONG (Universiti malaysia sarawak (UNIMAS), 2005)
SUMMARIZATION IS ONE SUCH TOOL THAT CAN HELP USERS TO QUICKLY DETERMINE THE MAIN POINTS OF A DOCUMENT. THIS REPORT DESCRIBES A NEW METHOD FOR TEXT SUMMARIZATION THAT ENABLES USERS TO FOCUS ON THE KEY CONTENT OF A DOCUMENT.THE TECHNIQUES PRESENT ARE APPLYING CERTAIN PROCESSING RESOURCES IN ANIE ASSIGNING WEIGHT TO EACH OF SETENCE AND LASTLY SELECTS THE SENTENCES THAT HAVE HIGHER WEIGHT. THE SELECTED SENTENCES ARE CONSIDERED AS A SUMMARY FOR THE INPUT TEXT. THE TECHNIQUE FOR SUMMARIZATION SHOUD BE APPLICABLE TO ANY SET OF TEXT DOCUMENTS.